(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to identify the (verbal communication The current study aims to identify the classroom communication skills of Arabic language teachers in preparatory schools. To achieve this goal, the researcher followed a descriptive approach as it is appropriate for the research objective. The researcher randomly selected(38) male and female teachers from the fourth preparatory grade out of a total population of(190) teachers and schools, representing(20%.) These teachers were distributed across(38) preparatory and secondary schools belonging to the education directorates in Baghdad city (Al-Karkh1, 2, 3 and Al-Rusafa1, 2, 3). The researcher used the random sampling method to select the preparatory and secondary day schools, and(38)schools were selected to represent the sample of teachers of Arabic language (the sample of the applied research, The researcher prepared a observation form for classroom communication skills that included three areas, with five main skills and(30) indicators that demonstrate the skills, The researcher used appropriate statistical methods to extract the research results, which showed that Arabic language teachers possess average classroom communication skills in their teaching performance.